Association of nonalcoholic fatty liver disease with serum vitamin D levels in combination of physical fitness in korean older adults. Issue 198 (April 2020) - Lee, Inhwan; Park, Eunmi; Cho, Jinkyung
Highlights: Low serum vitamin D levels were associated with non-alcoholic fatty liver disease (NAFLD) in older adults. Higher physical fitness levels were inversely associated with NAFLD in older adults. Serum vitamin D levels (≥30 ng/ml) and high physical fitness had additive effects on reducing the risk of NAFLD. Abstract: The prevalence of non-alcoholic fatty liver disease (NAFLD) tends to increase with age, but little is known regarding relations between the risk of NAFLD in older adults and serum vitamin D (25-hydroxyvitamin D) and physical fitness levels. The aim of this study was to investigate the relationship between NAFLD risk and serum vitamin D levels combined with physical fitness in elderly adults using a non-invasive diagnostic approach. We enrolled 533 Korean older adults (80.8 % women), aged 65 years or older in this cross-sectional study. NAFLD in absence of another cause of liver disease was defined according to the ZJU and NAFLD liver fat (LFS) score. Physical fitness was assessed using a senior fitness test protocol. Logistic regression analysis was used to estimate odds ratios (ORs) and 95 % confidence intervals (CIs) of NAFLD for different combinations of serum vitamin D and physical fitness levels. According to the ZJU (OR: 3.073, CI: 1.285–7.350, p = 0.012) and LFS (OR = 2.443, CI = 1.071–5.572, p = 0.034), individuals with serum vitamin D < 30 ng/ml and poor physical fitness had a significantly higher risk of NAFLD than individuals with serum vitamin D ≥ 30 ng/ml and high fitness (reference, OR = 1), even after adjustments for age, sex, smoking, alcohol consumption and physical inactivity. However, there was no significant association after adjustment for additional metabolic diseases. Our findings suggest that the maintenance of appropriate levels of serum vitamin D and/or high physical fitness and the monitoring metabolic diseases can help reduce the risk of NAFLD in older adults.